Brazil : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1998)
This paper describes major economic developments in Brazil in 1997. A number of issues were analyzed in the paper, including the slow progress being made in the negotiation of the fiscal adjustment programs with the states, the sustainability of the growing current account deficit, as well as the strength of the banking system following macroeconomic stabilization. The paper discusses the post-Real crisis in the states and the state adjustment programs being negotiated with the federal government. Privatization and the associated foreign direct investment flows are also described.